Gestão para a sustentabilidade e desempenho em empresas do setor mineral - Kneipp, Jordana Marques (2012)
Business competitiveness is increasingly linked to a sustainability-oriented management. The aim of this study was to analyze the influence of sustainability-oriented management in the Brazilian mining industry. Sustainability-oriented management was analyzed under two perspectives. First, we tried to identify the conditions that favor the integration of sustainability in the business strategy from the model of Lacy et al. (2010). Next, we analyzed the sustainability-oriented management practices based on the ten principles of sustainable growth in the mining industry defined by the International Council on Mining and Metals (ICMM, 2008). Business performance was evaluated based on performance indicators proposed by the Global Reporting Initiative GRI (2006, 2010b). The study was performed in two different methodological steps. The first phase of the study was characterized as qualitative and was conducted based on exploratory interviews with three companies in the mining industry in the states of Rio Grande do Sul and Minas Gerais. The results of this phase indicated that, in the analyzed companies, the integration of sustainability with the strategy is still a recent concern and is targeted primarily to meeting legal requirements. We can noticed a greater targeting of the companies analyzed in respect to the adoption of social management practices. The environmental management practices seek to basically meet the legal and market requirements. We further observed that there is no standardization or consolidation regarding the use of indicators for performance evaluation and dissemination of social and environmental actions of companies in the mining industry. The second stage of the study was characterized as quantitative and included carrying out a survey to examine the relationship between the adoption of management practices for sustainability and business performance. Overall, we found that there are positive associations between factors related to management practices for sustainability and business performance. Comparing the larger and smaller companies, it was not possible to find differences in the number of associations, however differences were found in the types of associated factors.